(untitled) (La U Investiga, 2017)
The sensory evaluation is a useful tool in the development of new products, which allows to identify the organoleptic characteristics of the products that are offered in the market. The objective of this research is to develop a new product based on an existing one and accepted in the market, improving its nutritional composition. In this case the commercial gummies were enriched, incorporating olive oil in their composition, to increase the contributions of omega 3 and 6, an experimental method was used in which several doses of oil were used reaching a final dose of 0.2ml For each 4g of gummies, the profile and taste star of the two samples were made, comparing the characteristics that changed, the sensory tests were performed, among them a discriminative one in which the duo-trio test was used, and one of type preferential using a hedonic scale, applied in children. As results, it was obtained that there are no statistically significant differences using a statistical analysis, with tables of ISO 10399 in the duo-trio test, and in the hedonic scale test it was obtained that the “I love” parameter was the answer of most children to whom the test was applied. It can be concluded that the gummies enriched with omegas 3 and 6 do not have significant differences in terms of their organoleptic characteristics and that they are accepted in the market as those currently offered.